Some aspects of the bone-muscle relationships in New Zealand lamb and mutton carcasses : a thesis presented at Massey Agricultural College in partial fulfilment of the requirements for the degree of Master of Agricultural Science in the University of New Zealand - Russel, A. J. F. (Massey University, 1961)
The three main constituents of a meat carcass are bone, musele, and fat, and of these the lean meat or muscle is of greatest interest and importance to the consumer. Bone represents an almost total waste and is hence considered as undesizable and as something which must be accepted with the desirable muscular tissue. In the words of Robert Bakewell, "You can't eat bone, therefore give the public something to eat." (Dawson, 1957). The Physical properties of muscle and bone are markedly different. Muscular tissue is compressible and hence difficult to ensure with accuracy on a linear scale. The intimate association of skeletal muscle with other tissues makes its complete removal for accurate weight estimation both difficult and tedious. Bony tissue, on the other hand, lends itself more readily to the measurement of linear dimensions and weight.
Best copy available.
Keywords: Sheep; Carcasses; Composition